APPROXIMATION OF FIXED POINT FOR F ITERATIVE ALGORITHM AND SOLUTION OF A DELAY DIFFERENTIAL EQUATION - Ashish Kumar; Bhokal, Ravi Parkash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper reports convergence, stability and data dependence results for the operators satisfying contractive conditions and contractive condition of rational expression using F iteration scheme in Banach space. With the help of suitable numerical examples, it is claimed that F iteration process is more efficient than many other iterative schemes available in literature. As an application, we have proposed solution to a delay differential equation. Our results are new and extends and improves many corresponding results available in the literature. Subject classification 47H10, 47H09, 49M05, 54H25